Study on the Evolution and Development of the Chinese Language and Writing System - Zhang, Huan; Bian, Zhengjie; Ma, Jiaqi; Xue, Fangyue (Transactions on Social Science, Education and Humanities Research, 2024)
This study explores the evolution and development of Chinese language and writing, focusing on the origins of Chinese characters, the development of ancient Chinese, and the evolution of modern Chinese. We examine the formation and evolution of ancient Chinese characters, including key periods such as oracle bone inscriptions and jinwen, as well as the standardization and popularization of modern Chinese, as exemplified by Putonghua and Mandarin. In addition, we study the development of written forms of Chinese characters, including the use of simplified and traditional characters. This study aims to gain a deeper understanding of the historical evolution of Chinese language and writing, so as to better understand the development of Chinese culture and society.